Dyadic adjustment and the relationship between sexual self-consciousness and sexual dysfunction in individuals with spinal cord injuries: a descriptive study - KOLAÇ, NURCAN (My University, 2022)
© The Academy of Spinal Cord Injury Professionals, Inc. 2022.Purpose: This study was conducted to determine the dyadic adjustment between individuals with SCI and their spouses and the relationship between their sexual self-consciousness and sexual life and to evaluate it according to the objectification theory. Method: This descriptive and cross-sectional study was conducted with 131 married individuals with SCI registered in the physical therapy and rehabilitation outpatient clinic of a university hospital between February 2020 and April 2021. The data of the study were collected using a Descriptive Information Form, the American Spinal Injury Association Impairment Scale (ASIA), the Dyadic Adjustment Scale (DAS), the Sexual Self-Consciousness Scale (SSCS), and the Arizona Sexual Experiences Scale (ASEX). In the study, the predictors of the sexual life of individuals with SCI were evaluated with the Stepwise Multiple Linear Regression analysis. In addition, predictors of sexual dysfunction in individuals with SCI were evaluated by the logistic regression analysis. The results were discussed within the framework of objectification theory. Results: According to the results of the study,.67.2% of the individuals with spinal cord injuries experienced sexual functionality problems; increased age, falling injuries, and being in ASIA grade A increased sexual self-awareness and sexual dysfunction; and being a male with SCI increased sexual focus. It was found that the adjustment between individuals with SCI and their spouses was a predictor that significantly reduced sexual embarrassment, sexual self-consciousness, and sexual dysfunction and that the strong adjustment between couples was an important factor for the prevention of sexual dysfunction development. Conclusion: It was found that most individuals with spinal cord injuries experienced sexual dysfunction. The importance of dyadic adjustment and sexual self-consciousness has come to the fore in the sexual life of these individuals.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Nöroloji (klinik); Neurology (clinical); Dyadic adjustment; Objectification theory; Sexual function; Sexual self-consciousness; Spinal cord injury; Spinal cord injury; Objectification theory; Sexual function; Sexual self-consciousness; Dyadic adjustment